Incidental Findings on Chest Computed Tomography Are Common and Linked to Inflammation in HIV-Infected Adults - Park, Michelle S (Antivir Ther, 2016)
BACKGROUND: Chest imaging is performed for a variety of reasons in HIV-infected adults. There are limited data on the prevalence of incidental findings, progression of these findings over time and the relationship with inflammation in antiretroviral therapy (ART)-treated HIV-infected adults. METHODS: This study utilized data from a randomized clinical trial of rosuvastatin in HIV-infected adults on ART. Incidental findings were reported from chest computed tomography (CT) scans obtained for coronary artery calcium score at entry, week 48 and 96. Markers of immune activation and inflammation were measured concurrently. Poisson Regression and generalized estimating equations were used. RESULTS: 147 participants were enrolled. Median age was 46 years, 78% were male, 68% African American and 63% current smokers. At baseline, 57% of participants had at least one incidental lung finding (ILF) and 4 additional participants had an at least one ILF by week 96. At baseline, older age, current smoking, lower nadir CD4+ T-cell count and low density lipoprotein and higher lipoprotein-associated phospholipase A2 (Lp-PLA2) were independently associated with having a greater number of ILFs. In the longitudinal analyses, older age, lower nadir CD4+ T-cell count and higher baseline soluble tumor necrosis factor α-receptor I (sTNF-RI) were independently associated with having a greater number of ILFs over 96 weeks. CONCLUSIONS: Over half of participants had at least one incidental finding on chest CT. Beyond traditional factors of older age and smoking, lower nadir CD4+ T-cell count and higher markers of inflammation were associated with having a greater number of ILFs in HIV-infected adults on ART.